If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2x = 3x + 7 + 1 + -8 Reorder the terms: 6 + 2x = 7 + 1 + -8 + 3x Combine like terms: 7 + 1 = 8 6 + 2x = 8 + -8 + 3x Combine like terms: 8 + -8 = 0 6 + 2x = 0 + 3x 6 + 2x = 3x Solving 6 + 2x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 2x + -3x = 3x + -3x Combine like terms: 2x + -3x = -1x 6 + -1x = 3x + -3x Combine like terms: 3x + -3x = 0 6 + -1x = 0 Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 5(12-3p)=1215p+60 | | -2(6-y)+4=-4 | | 9+3p-2=9p+25-4p | | x+-8=-8+3x | | 65m+50=45m+90 | | 8x+16=5x | | 90+.20x=50+.70x | | y-4x=17 | | 3x-12+4x-14=30 | | 2(2x-1)+3=9 | | 13=k/7 | | 7x-7=13+12 | | -61=d+[-18] | | 3(x+5)+3=3x+8 | | 8x-3=5+4(2x-2) | | 3-5x=10+x | | 4(-6)+10=2(n-7)-6 | | -11-7b=-7(b+2) | | -4(a-3)-(a+6)=1-8a+5+7a | | (3x-4)(2x+11)=0 | | -8+3-6x+6=-7x-2 | | 9x^2-17x-30= | | -8=-2+3/4x | | -3(4y-8)=-36 | | 30+5x+6x=30x | | 2x^4-128x=0 | | 351=3b | | 0.19y+0.05(y+7000)=2030 | | 3(-7a+6)-6a=-2a+18 | | Ax+r=5 | | 325-m=1500+2(m-500) | | 11x+8-30-x=-2(2x+4)-3(2x-2) |